2017
DOI: 10.15389/agrobiology.2017.1.129eng
|View full text |Cite
|
Sign up to set email alerts
|

ECOLOGICAL AND GENETIC EVALUATION OF MORPHOLOGICAL AND BIOCHEMICAL CHARACTERS OF QUALITY IN Brassica rapa L. ACCESSIONS FROM VIR COLLECTION

Abstract: A b s t r a c tPeculiarity of chemical composition of Brassica rapa L. crops (high water content and low content of fats) determine their low-calorie character. They are notable for relatively high content of carbohydrates and proteins, including all essential amino acids. Biochemical composition varies greatly among B. rapa members. We are the first to carry out a multifactor evaluation of valuable morphological and biochemical traits of B. rapa accessions from the core collection of Vavilov Institute of Plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…24,[28][29][30]33,45 In general, those screenings revealed high variations in the aliphatic GLSs 3 and 5, and the indole GLS 12 to be dominant in B. rapa. [28][29][30]33 Artemyeva et al 38 previously found correlations between shoot dry matter and chlorophyll, ascorbic acid and carotenoid content, depending on growing conditions in the studied B. rapa collection. To check whether a correlation exists between fresh weight and GLS concentration, a Pearson correlation analysis was performed.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…24,[28][29][30]33,45 In general, those screenings revealed high variations in the aliphatic GLSs 3 and 5, and the indole GLS 12 to be dominant in B. rapa. [28][29][30]33 Artemyeva et al 38 previously found correlations between shoot dry matter and chlorophyll, ascorbic acid and carotenoid content, depending on growing conditions in the studied B. rapa collection. To check whether a correlation exists between fresh weight and GLS concentration, a Pearson correlation analysis was performed.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…Profiling of GLS metabolites was conducted in leaves of 91 B. rapa accessions to complement a recent evaluation of this collection on morphological, biochemical, and genetic factors. 38 The leaves of these accessions showed great variety in size, shape, color, and texture. The average fresh weight (FW) differed from 1.00 g in VIR P-143 to 8.48 g in VIR 132.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine genotype-phenotype correlations in germplasm collections, association mapping using mostly SSR markers have been performed in B. rapa, B. oleracea and R. sativus accessions with respect to agronomic traits and morphological characteristics: bolting time, growth related traits, morphological characters connected with quality and productivity (Artemyeva et al, 2013) as well as biochemical traits: content of dry matter, sugars, protein, ascorbic acid, carotenoids, chlorophylls (Artemyeva et al, 2016(Artemyeva et al, , 2017. For instance, in B. rapa the most important loci are located on the top of chromosome A02, on the bottom of A03, in the higher region of A10 that correspond to BrFLC2, BrFLC5, BrFLC1 positions, supporting the importance of flowering time for the development of many morphological and biochemical traits in Brassica crops.…”
Section: Current Status Of B Oleracea and B Rapa Vegetable Collectionsmentioning
confidence: 99%
“…Morphological and biochemical traits linked to consumer value of 96 B. rapa accessions from different morphotypes from the VIR core collection were screened in the field and under greenhouse conditions in the North-West Russia and in the field in South China. The study revealed correlations between characteristics, and sources for breeding and genetic markers for traits investigated (Artemyeva et al, 2017). A study of the morphological traits of the plant, leaf lamina and root of 16 local Scandinavian turnip accessions from the VIR collection allowed determination of typical (cvs.…”
Section: Phenotypic Appearancementioning
confidence: 99%